NURSE'S POST-TRAUMATIC GROWTH DURING THE COVID-19 PANDEMIC IN HOSPITAL SETTINGS: LITERATURE REVIEW - Yudho Tri Handoko; Nurfika Asmaningrum; Anisah Ardiana (UPT Penerbitan Universitas Jember, 2023)
Introduction: The condition of the Covid 19 Pandemic affects the trauma of nurses so in their efforts to survive in nursing services it is important to explain in this study. Purpose: This study aims to analyze Post Traumatic Growth in nurses during the Covid-19 pandemic and post-traumatic growth subscriptions during the Covid-19 pandemic in the Hospital. Methods: Literature Review using three electronic databases such as PubMed, Science Direct and Google Scholar. The quality of the above articles is assessed based on JBI and MMAT. Result: A total of 2,614,019 articles were identified. Fifteen articles that have been analyzed found factors that influence Post Traumatic Growth including Age, gender, education, workload, gender and fear due to transmission of Covid-19. Hospitals must have good Post Traumatic Growth management so that nurses who have experienced trauma during a pandemic experience a faster post traumatic growth phase so they can positively assess the trauma they have experienced. Family support, social support are predictors for accelerating post-trauposttraumaticDiscussion It is important to implement Post Traumatic Growth (PTG) management for nurses to achieve survival in the face of the Covid 19 pandemic crisis. Conclusion: . Post traumatic growth will be used as a hospital evaluation for all health workers, especially nurses who have experienced trauma related to their work environment to improve nurse performance.